Diplomatische Studien zu den St. Galler Privaturkunden des frühen Mittelalters (ca. 720-980) - Zeller, Bernhard (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
Up to the present day more than 800 early medieval charters, dating from before 1000, have been preserved in the archive of the former Abbey of St Gall. This book offers the first comprehensive diplomatic analysis of this extraordinary collection of original documents.